Pension Policies in a Model with Endogenous Fertility - Giam Pietro Cipriani; Francesco Pascucci (Institute of Labor Economics (IZA), 2018)
We set up an overlapping generations model with endogenous fertility to study pensions policies in an ageing economy. We show that an increasing life expectancy may not be detrimental for the economy or the pension system itself. On the other hand, conventional policy measures, such as increasing the retirement age or changing the social security contribution rate could have undesired general equilibrium effects. In particular, both policies decrease capital per worker and might have negative effects on the fertility rate, thus exacerbating population ageing.
Keywords: D15; H55; J13; J18; J26; 330; overlapping generations; pension policies; endogenous fertility; ageing